A Technology Study on the Late Neolithic Pottery of Hakemi Use, Southeastern Türkiye - Natalia Petrova; Halil Tekin (Anadolu Araştırmaları)
Hakemi Use is a mound settlement on the right bank of the Tigris, within the borders of Diyarbakır province in southeast Türkiye. Within the scope of the Ilısu Dam Project built on the Tigris River, field studies were carried out between 2001-2012. The existence of two periods, Late Assyrian and Late Neolithic, was determined. The main cultural deposit in the mound covers the period known as Hassuna/ Samarra in the traditional cultural definition of Mesopotamia. Both material culture and 14C results show that the settlement was inhabited between 6100-5950 BCE. Approximately 25,000 pottery sherds were collected in five building levels of the Late Neolithic Period. Comprehensive studies on these sherds continue both typologically and technologically. In this study, various recipes for pottery paste, mineral, and organic admixture (including dung), different construction methods of ceramics, including using molds (textile and skin prints have been found), and other stages of ceramics manufacturing were studied in the pottery of the Late Neolithic Period of Hakemi Use. The production technology of different ceramic groups and other contemporary Mesopotamian sites were compared.